An astrologer at work in late medieval France : the notebooks of S. Belle - Carvalho, Helena Avelar de, 1964-2021 (Time, astronomy, and calendars, 2021)
"This book explores the notebooks of S. Belle, an astrologer who lived in late fifteenth-century France, as a case study of late medieval astrological practice. These notebooks combine astrological doctrine, a large collection of horoscopes, an almanac, and three complete judgements of nativities. By studying Belle's methods, processes of learning, and practices, this book contributes to a better understanding of the internal architecture of astrology in the pre-modern world; this includes its techniques, methodologies, goals, transmission, and development throughout history. It offers an internalist view of the practice of astrology, as a counterpart to the existing research into astrology's social and cultural impact"--